Media Framing in the Digital Age: A Narrative Review of Sociopolitical and Cultural Impacts - Hutagalung, Maasyithah; Nurhasanah (Indonesian Scientific Publication, 2025)
This narrative review analyzes how media framing in both news outlets and digital platforms shapes public perception across sociopolitical and cultural contexts. Drawing on framing theory as the conceptual foundation, this study systematically reviewed 72 peer-reviewed articles published between 2018 and 2023, retrieved from Scopus, Web of Science, and Google Scholar using Boolean operators and targeted keywords such as “media framing,” “public opinion,” “misinformation,” and “crisis communication.” The review identified three dominant themes: (1) the direct influence of framing on individual attitudes and behaviors, (2) cross-cultural variations in framing reception and impact, and (3) the systemic role of media in shaping policy discourses and institutional trust. The analysis demonstrates that linguistic strategies such as metaphors and emotional cues significantly alter public interpretation and engagement, with implications for both democratic processes and health communication. Unlike previous reviews, this study emphasizes cross-regional comparisons, particularly in developing countries, and highlights long-term behavioral implications often overlooked in prior research. The findings suggest that media framing holds transformative power, underscoring the need for ethical attention from practitioners and strategic policymaking. Strengthening media literacy programs and integrating cross-cultural perspectives are crucial steps to mitigate risks and leverage framing’s potential for social good.